2022
DOI: 10.31580/pjmls.v5i2.2510
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice Survey on Body Posture Among Undergraduate Physiotherapy Students

Abstract: Background: Posture is the alignment or orientation of body segments by maintaining an upright position. The postural deviations associated with change in young people’s behavior have increased. Incorrect posture refers to an irregular state of the body in which the body does not sustain a steady state and tissues and organs function normally in an erect position. Objective: The objectives of this study were to check the knowledge about body posture, attitude towards good and bad posture and practice for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Knowledge was assessed by exploring the respondent's familiarity with different body postures while carrying out their daily activities. In this study, 63.2% had knowledge about good posture; this is consistent with the findings of Kousar et al, [7] on knowledge, attitude and practice of posture among physiotherapy students where a significant number of the participants (80%) had good knowledge about their posture. Also consistent with the findings of Ephraim-Emmanuel et al, [16] on knowledge, attitude and practice of preventing the occurrence of work-related musculoskeletal disorders among Doctors in University of Port-Harcourt Teaching Hospital where they found that majority of their respondents (96.4%) had good knowledge of musculoskeletal system disorders' prevention at work.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Knowledge was assessed by exploring the respondent's familiarity with different body postures while carrying out their daily activities. In this study, 63.2% had knowledge about good posture; this is consistent with the findings of Kousar et al, [7] on knowledge, attitude and practice of posture among physiotherapy students where a significant number of the participants (80%) had good knowledge about their posture. Also consistent with the findings of Ephraim-Emmanuel et al, [16] on knowledge, attitude and practice of preventing the occurrence of work-related musculoskeletal disorders among Doctors in University of Port-Harcourt Teaching Hospital where they found that majority of their respondents (96.4%) had good knowledge of musculoskeletal system disorders' prevention at work.…”
Section: Discussionsupporting
confidence: 92%
“…Healthy posture is the state of muscle and skeletal equilibrium that protects the body structures independently of attitude (erect, sitting, stooping, bend) or in which these structures are functioning or resting against injury or progressive deformity. In such situation's muscles function more effectively and thoracic and abdominal organs are given optimal position [7]. Bad posture can cause fatigue, muscular strain and can cause pain in later stages.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, participants in another study of physiotherapy students had inadequate ergonomic skills in their practice (Kousar et al, 2022). Moreover, only 4.6% of dental students practiced good ergonomics (El-sallamy et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…According to El-sallamy et al, 2018, nearly half of the dentistry students have fair ergonomics knowledge, with 84.8% having a positive attitude towards ergonomics but only 4.5% practicing good ergonomics. Similarly, good knowledge of ergonomics and a positive attitude towards ergonomics was reported among physiotherapy undergraduate at the University Institute of Physical Therapy in Pakistan (Kousar et al, 2022). However, these students were noted not to practice good ergonomics (Kousar et al, 2022).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation